Hydrogeochemical zoning of uranium isotopes (234U/ 238U) in the Southern Siberian paleocontinent: the role of the South Baikal reservoir in the groundwater formation - S. V. Rasskazov; A. M. Ilyasova; I. S. Chuvashova; S. A. Bornyakov; A. I. Orgilyianov; S. N. Kovalenko; A. K. Seminsky; E. P. Popov; E. P. Chebykin (Геодинамика и тектонофизика, 2020)
The southern deformed edge of the Siberian paleocontinent is studied for zoning the disturbance of 234U/238U cyclic equilibrium in groundwaters discharged to the accreted Khamardaban terrane. A relationship is established between vertical variations of 234U/238U (ОА4/8) activity ratios and the hydrogeochemical zoning of groundwaters. Lateral ОА4/8 zoning of groundwaters in the basement rocks and sedimentary cover of the Siberian platform is described. It is emphasized that an important role is played by the water propagating from the South Baikal reservoir (SBR) (ОА4/8 = 1.95–1.99; U content = 0.44–0.46 μg/L) under the shore of Lake Baikal. It is suggested that the lateral advancement of the SBR water is facilitated by the development of low-angle (weakened by rifting) fractures of the Angara thrust fault, as well as subvertical fractures in the shear zone of the Main Sayan Fault. Monitoring data on the study area show that the ratios of the groundwaters components vary in time due to Cherdyntsev – Chalov deformational effect, chemical interaction of the waters and evaporites, and mixing of the groundwaters with contrasting hydrogeochemical signatures.